Development of a new Quantum Trajectory Molecular Dynamics Framework - Svensson, Pontus (Cranfield University, 2023)
In this work, we investigate matter under extreme conditions, the systematic study of which has only been possible due to the establishment of high-power laser facilities in the last decades. These states of matter are of interest for larger astronomical objects, but in particular for engineering systems for man-made nuclear fusion through high density, e.g. inertial confinement fusion, a concept for nuclear energy production based on commonly available elements. The property of matter under these conditions is largely unknown, hindering further technical development. Specifically, we examine plasma in the warm dense matter regime through numerical computation, a theoretically challenging regime as it is the transition from a cold dense system to a hot dense one. Therefore, neither the assumptions for cold nor hot systems are appropriate and everything should be accounted for. We utilise a quantum mechanical description -quantum mechanics being the microscopic theory of everything from molecules to metals - but for the high-temperature states under consideration characteristics of a plasma emerge. The particular problem we are addressing is related to the large electron-proton mass ratio, where even the lightest nucleus, the hydrogen ion, is almost 2000 times more massive than the electron resulting in very different velocities for ions and electrons. This is problematic, as to describe the ion motion, the computational costly description of electrons needs to be carried out for a long time. We address this with wave packet molecular dynamics describing the time evolution explicitly, impotent for the description of dynamical properties.
Keywords: Warm dense matter; Wave packet molecular dynamics; Born-Oppenheimer approximation; DSDS22 Poster; DSDS22